THE ANALYSIS OF FACTORS AFFECTING AUDITOR PERFORMANCE WITH AUDITOR WORK EXPERIENCES AS MODERATING VARIABLES IN PUBLIC ACCOUNTANT OFFICE AUDITORS IN MEDAN - Syauqi, Teuku Radhifan (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objectiveof the research was to analyze the influence of auditor’s work motivation, auditor’s work satisfaction, and auditor’s work discipline on auditor’s performance with auditor’s work experience as moderating variable in the public accountant office,  Medan. The research used causality method with saturated or census sampling technique. Primary data were gathered by distributing questionnaires to 87 auditing staffs at the public accountant office, Medan. Hypothesis was tested by using multiple linear regression analysis, F-test, t-test and residual test with an SPSS software program. The result of the research showed that, simultaneously, auditor’s work motivation, auditor’s work satisfaction and auditor’s work discipline had significant influence on auditor’s performance. Partially, the variables of auditor’s work motivation, auditor’s work satisfaction and auditor’s work discipline had positive and significant influence on auditor’s performance. Auditor’s work experience could not moderate the correlation of auditor’s work motivation, auditor’s work satisfaction and auditor’s work discipline with auditor’s performance at the Public Accountant Office, Medan.